It's All Areas!

Level pending

In right A B C , m A B C = 3 0 , A D = x , D B = 3 x \triangle{ABC}, m\angle{ABC} = 30^{\circ}, \overline{AD} = x, \overline{DB} = 3x and the quarter of the circle has radius C E = 2 x 2 \overline{CE} = 2x - 2 .

If the sum of the areas A 1 + A 2 = a ( b + c a ( d + e a ) π ) A_{1} + A_{2} = a(b + c\sqrt{a} - (d + e\sqrt{a})\pi) , where a , b , c , d a,b,c,d and e e are coprime positive integer, find a + b + c + d + e a + b + c + d + e .


The answer is 52.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

David Vreken
Jan 7, 2021

Let the point to the left of E E be H H , and let B E = y BE = y .

Since A B C = 30 ° \angle ABC = 30° and A B = 4 x AB = 4x , from A B C \triangle ABC we have A C = 2 x AC = 2x and B C = 2 3 x = 2 x 2 + y BC = 2\sqrt{3}x = 2x - 2 + y .

By the tangent-secant theorem , ( 3 x ) 2 = y ( 4 x 4 + y ) (3x)^2 = y(4x - 4 + y) .

These two equations solve to x = 4 + 2 3 x = 4 + 2\sqrt{3} and y = 6 + 4 3 y = 6 + 4\sqrt{3} .

That means A C = 2 x = 2 ( 4 + 2 3 ) = 8 + 4 3 AC = 2x = 2(4 + 2\sqrt{3}) = 8 + 4\sqrt{3} and E C = 2 x 2 = 2 ( 4 + 2 3 ) 2 = 6 + 4 3 EC = 2x - 2 = 2(4 + 2\sqrt{3}) - 2 = 6 + 4\sqrt{3} .

Since H B E = 30 ° \angle HBE = 30° and B E = y = 6 + 4 3 BE = y = 6 + 4\sqrt{3} , from H B E \triangle HBE we have H E = 3 3 ( 6 + 4 3 ) = 4 + 2 3 HE = \frac{\sqrt{3}}{3}(6 + 4\sqrt{3}) = 4 + 2\sqrt{3} .

The sum of the areas A 1 + A 2 A_1 + A_2 is the difference between the areas of trapezoid A H E C AHEC and the quarter circle, so:

A 1 + A 2 = 1 2 ( A C + H E ) E C 1 4 π E C 2 A_1 + A_2 = \frac{1}{2}(AC + HE) \cdot EC - \frac{1}{4}\pi\cdot EC^2

A 1 + A 2 = 1 2 ( 8 + 4 3 + 4 + 2 3 ) ( 6 + 4 3 ) 1 4 π ( 6 + 4 3 ) 2 A_1 + A_2 = \frac{1}{2}(8 + 4\sqrt{3} + 4 + 2\sqrt{3}) \cdot (6 + 4\sqrt{3}) - \frac{1}{4}\pi\cdot (6 + 4\sqrt{3})^2

A 1 + A 2 = 3 ( 24 + 14 3 ( 7 + 4 3 ) π ) A_1 + A_2 = 3(24 + 14\sqrt{3} - (7 + 4\sqrt{3})\pi) .

Therefore, a = 3 a = 3 , b = 24 b = 24 , c = 14 c = 14 , d = 7 d = 7 , e = 4 e = 4 , and a + b + c + d + e = 52 a + b + c + d + e = \boxed{52} .

Interestingly, H E = A D HE = AD .

David Vreken - 5 months ago

I found the same answer, however, I was a little bit confused by the sentence "coprime positive integers" because a and b, or b and e are not coprime integers each other.

Gerard Boileau - 5 months ago

Log in to reply

I took it to mean that gcd(a, b, c, d, e) = 1

David Vreken - 5 months ago
Rocco Dalto
Jan 6, 2021

A F = 2 x ( 2 x 2 ) = 2 , G D = 3 2 x , A G = x 2 AF = 2x - (2x - 2) = 2, \overline{GD} = \dfrac{\sqrt{3}}{2}x, \overline{AG} = \dfrac{x}{2} \implies

( C D ) 2 = 4 ( x 1 ) 2 = 16 x 2 32 x + 16 = ( 2 x x 2 ) 2 + 3 4 x 2 = 12 x 2 x 2 8 x + 4 = 0 x = 4 ± 2 3 (\overline{CD})^2 = 4(x - 1)^2 = 16x^2 - 32x + 16 = (2x - \dfrac{x}{2})^2 + \dfrac{3}{4}x^2 = 12x^2 \implies x^2 - 8x + 4 = 0 \implies x = 4 \pm 2\sqrt{3}

x = 4 2 3 2 ( x 1 ) = 2 ( 3 2 3 ) < 0 x = 4 - 2\sqrt{3} \implies 2(x - 1) = 2(3 - 2\sqrt{3}) < 0 \therefore choose x = 4 + 2 3 x = 4 + 2\sqrt{3}

\implies radius r = 2 x 2 = 2 ( 3 + 2 3 ) r = 2x - 2 = 2(3 + 2\sqrt{3})

For A 2 A_{2} :

Let θ = m D C E \theta = m\angle{DCE}

tan ( θ ) = 3 θ = π 3 A s e c t o r C D E = 1 2 θ r 2 = 1 2 ( π 3 ) ( 4 ) ( 3 + 2 3 ) 2 = \implies \tan(\theta)= \sqrt{3} \implies \theta = \dfrac{\pi}{3} \implies A_{sector{CDE}} = \dfrac{1}{2}\theta r^2 = \dfrac{1}{2}(\dfrac{\pi}{3})(4)(3 + 2\sqrt{3})^2 =

2 π ( 7 + 4 3 ) 2\pi(7 + 4\sqrt{3})

and A C D I = 1 2 ( 3 x 2 ) ( 3 2 x ) = 3 3 8 x 2 = A_{\triangle{CDI}} = \dfrac{1}{2}(\dfrac{3x}{2})(\dfrac{\sqrt{3}}{2}x) = \dfrac{3\sqrt{3}}{8}x^2 = 3 3 8 ( 4 + 2 3 ) 2 \dfrac{3\sqrt{3}}{8}(4 + 2\sqrt{3})^2 = 3 3 2 ( 7 + 4 3 ) = \dfrac{3\sqrt{3}}{2}(7 + 4\sqrt{3})

Let R 2 R_{2} be region D E I A R 2 = A s e c t o r C D E A C D I = ( 7 + 4 3 ) ( 4 π 3 3 ) 2 DEI \implies A_{R_{2}} = A_{sector{CDE}} - A_{\triangle{CDI}} = \dfrac{(7 + 4\sqrt{3})(4\pi - 3\sqrt{3})}{2}

B C = 2 3 x B E = 2 3 x ( 2 x 2 ) = 2 ( ( 3 1 ) x + 1 ) = \overline{BC} = 2\sqrt{3}x \implies \overline{BE} = 2\sqrt{3}x - (2x - 2) = 2((\sqrt{3} - 1)x + 1) =

2 ( 2 3 + 3 ) 2(2\sqrt{3} + 3) and A D G H B E 1 3 = H E 2 ( 2 3 + 3 ) H E = 4 3 + 6 3 = \triangle{ADG} \sim \triangle{HBE} \implies \dfrac{1}{\sqrt{3}} = \dfrac{\overline{HE}}{2(2\sqrt{3} + 3)} \implies \overline{HE} = \dfrac{4\sqrt{3} + 6}{\sqrt{3}} = 4 + 2 3 = x 4 + 2\sqrt{3} = x and D I = 3 x 2 = 3 ( 2 + 3 ) DI = \dfrac{3x}{2} = 3(2 + \sqrt{3}) and I E = C E C I = IE = \overline{CE} - \overline{CI} =

( 4 3 2 ) x 2 = 3 + 2 3 (\dfrac{4 - \sqrt{3}}{2})x - 2 = 3 + 2\sqrt{3} \implies area of trapezoid

A D H E I = 1 2 ( 5 ) ( 2 + 3 ) ( 3 + 2 3 ) = 5 2 ( 12 + 7 3 ) A_{DHEI} = \dfrac{1}{2}(5)(2 + \sqrt{3})(3 + 2\sqrt{3}) = \dfrac{5}{2}(12 + 7\sqrt{3})

A 2 = A D H E I A R 2 = 48 + 28 3 ( 14 + 8 3 ) π \implies \boxed{A_{2} = A_{DHEI} - A_{R_{2}} = 48 + 28\sqrt{3} - (14 + 8\sqrt{3})\pi}

For A 1 : A_{1}:

m F C D = π 6 A s e c t o r C D F = 1 2 ( π 6 ) ( 4 ) ( 3 + 2 3 ) 2 = π ( 7 + 4 3 ) m\angle{FCD} = \dfrac{\pi}{6} \implies A_{sector{CDF}} = \dfrac{1}{2}(\dfrac{\pi}{6})(4)(3 + 2\sqrt{3})^2 = \pi(7 + 4\sqrt{3})

and A D G C = 3 3 2 ( 7 + 4 3 ) A_{\triangle{DGC}} = \dfrac{3\sqrt{3}}{2}(7 + 4\sqrt{3})

Let R 1 R_{1} be region F D G A R 1 = A s e c t o r C D F A D G C = FDG \implies A_{R_{1}} = A_{sector{CDF}} -A_{\triangle{DGC}} = ( 7 + 4 3 ) ( 2 π 3 3 ) 2 \dfrac{(7 + 4\sqrt{3})(2\pi - 3\sqrt{3})}{2}

and A A D G = 3 8 x 2 = 3 2 ( 7 + 4 3 ) A_{\triangle{ADG}} = \dfrac{\sqrt{3}}{8}x^2 = \dfrac{\sqrt{3}}{2}(7 + 4\sqrt{3})

A 1 = A A D G A R 1 = ( 7 + 4 3 ) ( 2 3 π ) = 24 + 14 3 ( 7 + 4 3 ) π \implies \boxed{A_{1} = A_{\triangle{ADG}} - A_{R_{1}} = (7 + 4\sqrt{3})(2\sqrt{3} - \pi) = 24 + 14\sqrt{3} - (7 + 4\sqrt{3})\pi}

A 1 + A 2 = 72 + 42 3 ( 21 + 12 3 ) π = 3 ( 24 + 14 3 ( 7 + 4 3 ) π ) = \implies A_{1} + A_{2} = 72 + 42\sqrt{3} - (21 + 12\sqrt{3})\pi = 3(24 + 14\sqrt{3} - (7 + 4\sqrt{3})\pi) =

a ( b + c a ( d + e a ) π ) a(b + c\sqrt{a} - (d + e\sqrt{a})\pi) a + b + c + d + e = 52 \implies a + b + c + d + e = \boxed{52} .

I found the same answer, however, I was a little bit confused by the sentence "coprime positive integers" because a and b, or b and e are not coprime integers each other.

Gerard Boileau - 5 months ago

Log in to reply

Coprime means the greatest common factor of all the integers is 1. Which is the case in this problem. Your thinking of pairwise positive integers.

Rocco Dalto - 5 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...